Friedel–Crafts alkylation reaction with fluorinated alcohols as hydrogen-bond donors and solvents. Issue 19 (13th March 2018) - Tang, Ren-Jin; Milcent, Thierry; Crousse, Benoit
Abstract : Friedel–Craft alkylation of heterocycle derivatives with β-nitroalkenes was performed in HFIP. The one-pot synthesis of tryptamines could be applied. Abstract : An effective and clean FC alkylation of indoles and electron-rich arenes with β-nitroalkenes in HFIP was reported. The desired products are formed rapidly in excellent yields under mild conditions without the need for any additional catalysts or reagents. Further, this methodology can be applied to one-pot synthesis of biologically active tryptamine derivatives.